Acceptance, experiences, and needs of hospitalized pregnant women toward an electronic mindfulness-based intervention: a pilot mixed-methods study - Schiele, Claudia; Götz, Maren; Haßdenteufel, Kathrin; Müller, Mitho; Graf, Johanna; Zipfel, Stephan; Wallwiener, Stephanie (Frontiers in psychiatry, 2022)
BackgroundAnxiety disorders and depression during pregnancy are highly prevalent. Hospitalized pregnant women with high maternal or fetal risk represent a particularly vulnerable population often excluded from research samples. Screening for mental health disorders is not routinely offered for this particular patient group. Electronic mindfulness-based interventions constitute an accessible, convenient, and cost-effective mental health resource but have not yet been evaluated for acceptance in inpatient settings. To date, little is known about the needs and perceptions of this group of women.ObjectiveThe aim of this study was to examine whether a brief electronic mindfulness-based intervention (eMBI) is accepted among hospitalized high-risk pregnant women. We assessed personal motivation and barriers, experiences, usability requirements, and overall acceptance of the eMBI, as well the specific needs and demands of patients with high-risk pregnancies regarding mental health services.MethodsAn exploratory pilot study with a mixed-methods study design was carried out among 30 women hospitalized with a high obstetric risk. The study participants were given access to an eMBI with a 1-week mindfulness program on how to deal with stress, anxiety, and depressive symptoms. Semi-structured interviews were conducted with the 30 participants and analyzed using systematic content analysis. In addition, acceptance and usability were assessed via questionnaires.ResultsStudy findings showed a high level of acceptance of the eMBI. Most of the respondents were satisfied with the usability and considered the eMBI program to be helpful. The greatest barriers to using the eMBI were a general negative attitude toward using apps, preference for personal contact, or no current need for psychotherapy. Participants criticized the lack of awareness of mental health issues during pregnancy and expressed a need for low-threshold treatment offers, especially during hospitalization.ConclusionsThere is a strong need for mental health services in pregnancy care, especially for pregnant women with risk profiles. An eMBI offers an acceptable means of providing mental health support for hospitalized women with a severe obstetric risk.